2019
DOI: 10.1186/s12938-019-0637-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound therapy on the synovial fluid proteome in a rabbit surgery-induced model of knee osteoarthritis

Abstract: Background Ultrasound (US) therapy may improve osteoarthritis symptoms. We investigated the effects of US on the synovial fluid (SF) proteome in a rabbit knee osteoarthritis (KOA) model to explore its therapeutic mechanisms. Methods Sixteen healthy 6-month-old New Zealand white rabbits (eight male, eight female), weighing 2.5–3.0 kg, were randomly divided into groups A and B with eight rabbits per group. Both groups were subjected to right anterior cruciate ligament tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…However, it has been identified in several other relevant proteomic studies that assessed (1) the membrane proteins of equine articular chondrocytes 23 ; (2) the secretome of cultured chondrocytes 29 ; (3) the SF of patients with either rheumatoid arthritis or OA 2 ; and (4) the SF of rabbits subjected to ACL transection compared with sham injury. 21 Together, these data suggest that this protein may be secreted from chondrocytes into the SF, but how changes in the abundance of this protein within the SF relate to OA disease severity or progression requires further investigation.…”
Section: Discussionmentioning
confidence: 86%
“…However, it has been identified in several other relevant proteomic studies that assessed (1) the membrane proteins of equine articular chondrocytes 23 ; (2) the secretome of cultured chondrocytes 29 ; (3) the SF of patients with either rheumatoid arthritis or OA 2 ; and (4) the SF of rabbits subjected to ACL transection compared with sham injury. 21 Together, these data suggest that this protein may be secreted from chondrocytes into the SF, but how changes in the abundance of this protein within the SF relate to OA disease severity or progression requires further investigation.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, more and more investigators focus on proteomics studies investigating the componence and potential roles of synovial uid [14,15,16,17,18]. Animal models of osteoarthritis are also used in recent studies to understand the pathophysiology of OA and develop successful treatment of OA [19,20]. However, the role of ST of the knee joint in the onset and development of OA remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, abundances of these uncharacterised proteins could not be validated using antibody methodologies. Recently, a study investigating the SF proteome of a surgeryinduced OA model in rabbits identified reduced levels of immunoglobulin heavy chain protein compared to sham controls (69). Immunoglobulins have previously been identified within superficial articular cartilage layers of a proportion of OA patients as well as elevated levels found within the synovial membrane of dogs diagnosed with cranial cruciate ligament rupture (70,71).…”
Section: Discussionmentioning
confidence: 99%